1999
DOI: 10.1039/a905014k
|View full text |Cite
|
Sign up to set email alerts
|

exo-Glycal approaches to C-linked glycosyl amino acid synthesis

Abstract: Two novel routes to C-linked glycosyl amino acids are described; the first involves elaboration of an exo-glycal and subsequent Ramberg-Bäcklund rearrangement of a sulfone intermediate to give, after functional group manipulation, a protected C-glycosyl serine, while the second uses hydroboration-Suzuki coupling of the same exo-glycal to produce ultimately the corresponding C-glycosyl asparagine analogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Scheme 12 presents a more elaborate method utilized to synthesize C-disaccharide 61, involving the sequential hydroboration of glycal 60 and triflate mediated Suzuki coupling [59]. Similar strategies were also reported by others [60][61][62]. Furthermore, our group reported a facile synthesis of spiro-sugars (Scheme 13) by hydroboration of exo-glycosyl dienes 62-64 [18,63], which favorably gave the α-isomers following an acidic workup.…”
Section: Application For C-glycoside Synthesissupporting
confidence: 52%
“…Scheme 12 presents a more elaborate method utilized to synthesize C-disaccharide 61, involving the sequential hydroboration of glycal 60 and triflate mediated Suzuki coupling [59]. Similar strategies were also reported by others [60][61][62]. Furthermore, our group reported a facile synthesis of spiro-sugars (Scheme 13) by hydroboration of exo-glycosyl dienes 62-64 [18,63], which favorably gave the α-isomers following an acidic workup.…”
Section: Application For C-glycoside Synthesissupporting
confidence: 52%
“…The stereoselective 9‐BBN hydroboration‐oxidation of 2a to give exclusively the β‐ C ‐glycoside 7 was initially described by RajanBabu and Reddy;3 Johnson and Johns have demonstrated that the intermediate organoborane can undergo palladium‐catalysed cross‐coupling reactions to give the aromatic C ‐glycoside derivatives 8 9. We have also recently reported the synthesis of a C ‐glycosyl amino acid by the Suzuki coupling of this organoborane with a vinyl iodide derived from the Garner aldehyde 10. In addition, we have carried out the dihydroxylation of exo ‐glycal 2a to produce the known tetrabenzyl‐α‐ D ‐ gluco ‐2‐heptulopyranose 9 {m.p.…”
Section: Resultsmentioning
confidence: 95%
“…This entailed a tandem boron‐mediated aldol addition [(−)‐Ipc 2 BCl, Et 3 N] and Sm‐promoted reduction (SmI 2 , EtCHO) sequence, proceeding via the alcohol intermediates 10 and 11 (53 %, 7 steps). The amine 12 was next coupled (EDC, HOBt) with 9 and the resulting amide cyclized to the oxazoline 3 (DAST, 73 %) . At this point, the lack of an electron‐withdrawing substituent on the oxazoline ring presented a potential problem, since the oxidation of unactivated oxazolines to the corresponding oxazoles can be challenging.…”
Section: Methodsmentioning
confidence: 99%